Effect of Back In Control (BIC) Program on the Level of Discipline in Children with Attention Deficit and Hyperactivity Disorder (ADHD) in Denpasar - Purnamayani, Ni Kadek Ayu (Coping: Community of Publishing in Nursing; Vol 1 No 2 (2013): JURNAL EDISI JULI-DESEMBER 2013, 2013)
Attention Deficit and Hyperactivity Disorder (ADHD) is a behavioral disorder that has a main symptom of an individual's inability to focus, impulsivity, and hyperactivity. Children with ADHD are not able to follow the existing rules, so they are known as a naughty child, dissidents and unable to take responsibility. Back In Control (BIC) program is one of the methods of behavior modification based on a system of rules. Parents are expected to create a system of rules that are tailored to target of expected behavior and are fully supervised by the whole family at home. This study aims to determine the effect of Back In Control (BIC) program on the level of discipline in children with Attention Deficit and Hyperactivity Disorder (ADHD) in Denpasar. This study used a Pre Experimental design-one group pre-test post-test without a control group. Sampling was carried out by total sampling which was to 14 respondents. Wilcoxon Signed Rank Test was used to analyze the data with 95% confidence interval. Results showed the majority level of discipline before the Back In Control (BIC) program was moderate as much as 13 respondents (92.86%), which was by seven respondents (50%) increased to be good and six respondents (42,85%) remained. Asymp sig (2-tailed) value or p-value of 0.005 (less than the ? value = 0.05) so H0 is rejected, it can be stated that there is a significant effect of  Back In Control (BIC) program on the level of discipline in children with Attention Deficit and Hyperactivity Disorder (ADHD) in Denpasar.
Keywords: Back In Control, Discipline, ADHD